2019
DOI: 10.1038/s41746-019-0088-y
|View full text |Cite
|
Sign up to set email alerts
|

Building digital innovation capacity at a large academic medical center

Abstract: Academic medical centers (AMCs) today prioritize digital innovation. In efforts to develop and disseminate the best technology for their institutions, challenges arise in organizational structure, cross-disciplinary collaboration, and creative and agile problem solving that are essential for successful implementation. To address these challenges, the Digital DesignLab was created at NYU Langone Health to provide structured processes for assessing and supporting the capacity for innovative digital development i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…As we found at our institution, the lack of a clear path to develop digital health technologies beyond telehealth was reflected in uncoordinated and siloed development largely unknown outside of the department or clinic that implemented it. This issue is one that all AMCs must tackle [13] if we are to realize the promise of these technologies to the health of our citizens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we found at our institution, the lack of a clear path to develop digital health technologies beyond telehealth was reflected in uncoordinated and siloed development largely unknown outside of the department or clinic that implemented it. This issue is one that all AMCs must tackle [13] if we are to realize the promise of these technologies to the health of our citizens.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true where the focus is on rural areas, and logistical hurdles to implementation are often extensive. Several AMCs have recognized these needs and have established digital institutes or centers that foster education, skill building, and cross-disciplinary team building to support quality care delivery solutions and research [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…5 In addition, a pilot study of academic and industry stakeholders’ attitude on technology disruption in behavioral health research found that weaknesses in one party are often complemented by strengths in the other. 12 For instance, academic partners are perceived to be less savvy with technology, an area in which industry partners generally excel. This was reflected in our study’s finding that stakeholders from both fields identified having complementary roles as the leading facilitator to collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…Prioritizing scientific evidence (13) Misaligned goals and expectations (14) Prioritizing business outcomes (12) Prioritizing business outcomes (11) Timeline (13) Timeline (14) Responses of the stakeholder affiliated with both academia and industry are included in both groups. Table 5.…”
Section: Barriersmentioning
confidence: 99%
See 1 more Smart Citation